If virilization syndrome in young women - Rodríguez, Washington (2015)
26 year old woman admitted to the Hospital for hirsutism and amenorrhea. Natural and from Lima married, office secretary. Menarche at 12 years of age; in a few months they became regular rules. At 20 years of age he presented a pregnancy came to term and then began using oral contraceptives for six months, suspended for having appeared the ankle edema. Three years before admission and reinstall the contraceptive medication for a year and a half before the query was using norgestrel 0.5 ethinyl estradiol 0.05. He began to have moderate acne and facial hair growth and thighs. Fifteen months before admission she discontinued the medication and follows hipomenorrea for three months and then amenorrhea. Le administered medroxyprogesterone acetate for five days, with day after a normal menstrual flow. Four months before admission increased facial hair and thighs. He consulted a gynecologist who intrapérvica found no abnormality. An X-ray was normal sella. Testosterone levels in serum were 2.8 and 2.6 ng / ml, 13.0 am cortisol ug / dl and DHEA-S 310 ug / dl.